Segmentasi Baris Lontar Dengan Metode A * Path Planning (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2022)
Historical documents in the form of ancient manuscripts are one form of the Indonesian nation's cultural heritage that deserves to be important, one of which is Lontar. Currently not many people can read the writings in palm leaves, therefore, ancient manuscript collectors have made efforts to digitize ancient manuscripts. The digitization of ancient manuscripts aims to improve the image quality of ancient manuscripts with the help of computers. Digitization requires an image quality improvement process by performing noise reduction and edge detection and line segmentation on digital images of ancient manuscripts. In this study, the noise reduction process uses the Mean Filter method, edge detection uses the Sobel operator, and line segmentation in this study uses the A * Path Planning Algorithm. Based on research conducted on 24 lontar images, line segmentation process obtained an accuracy of 95%.